Chloroplastic Os3BGlu6 contributes significantly to cellular ABA pools and impacts drought tolerance and photosynthesis in rice. Issue 4 (11th February 2020) - Wang, Chengliang; Chen, Shuai; Dong, Yanping; Ren, Ruijuan; Chen, Defu; Chen, Xiwen
Summary: Cellular abscisic acid (ABA) concentration is determined by both de novo biosynthesis and recycling via β‐glucosidase(s). However, which rice β‐glucosidase(s) are involved in this process remains unknown. Here, we report on a chloroplastic β‐glucosidase isoenzyme, Os3BGlu6, that functions in ABA recycling in rice. Disruption of Os3BGlu6 in rice resulted in dwarfism, lower ABA content in leaves, drought‐sensitivity, lower photosynthesis rate and higher intercellular CO2 concentration. Os3BGlu6 could hydrolyze ABA‐GE to ABA in vitro . The reversion and overexpression rice lines restored or increased the drought tolerance as shown by the higher β‐glucosidase activity, ABA concentrations and expressions of ABA‐ and drought‐responsive genes. Drought induced Os3BGlu6 to form dimers, and the degree of polymerization correlated well with the increase in cellular ABA concentrations and drought tolerance in rice. Os3BGlu6 was responsive to drought and ABA treatments, and the protein was localized to the chloroplast. Disruption of Os3BGlu6 resulted in the increased stomatal density and impaired stomatal movement. Transcriptomics revealed that disruption of Os3BGlu6 resulted in chloroplastic oxidative stress and lowered Rubisco activity even under normal conditions. Taken together, these results suggest that chloroplastically localized Os3BGlu6 significantly affects cellular ABA pools, thereby affecting drought tolerance and photosynthesis in rice.